Writing Tricksters : Mythic Gambols in American Ethnic Fiction. - Smith, Jeanne Rosier (University of California Press, 2022)
Writing Tricksters examines the remarkable resurgence of tricksters--ubiquitous shape-shifters who dwell on borders, at crossroads, and between worlds--on the contemporary cultural and literary scene. Depicting a chaotic, multilingual world of colliding and overlapping cultures, many of America's most successful and important women writers are writing tricksters. Taking up works by Maxine Hong Kingston, Louise Erdrich, and Toni Morrison, Jeanne Rosier S.